Esophageal cancer and human papillomavirus-16 in a patient undergoing renal transplantation in Hospital Edgardo Rebagliati-Martins, Lima, Peru: first report in Latin America and literature review - Huamán Guerrero, Manuel (2018)
Introduction: Being multifactorial is a clearly recognized feature of cancer in humans. Recently, some members of the human papillomavirus family have been associated as conditioning factors for the development of epidermoid esophageal carcinoma.Clinical case: This is the first case described in Latin America of an esophageal cancer with the presence of a human papillomavirus-16 in a patient undergoing renal transplantation. This patient, a 59-year old woman, had a renal transplant eleven years ago because of a nephritic syndrome with an unknown cause. She received immunosuppression using cyclosporine, prednisone and mycophenolate, never interrupting therapy. Three months before diagnosis, the patient presented with dysphagia to solid foods, associated to weight loss. An upper gastrointestinal endoscopy showed the presence of a proliferative ulcerated lesion in the middle third of the esophagus. A biopsy of this lesion showed an epidermoid carcinoma. A PCR study looking for human papillomavirus-16 performed in tumor tissue was reported as positive.